Holocene Vegetation Succession and Response to Climate Change on the South Bank of the Heilongjiang-Amur River, Mohe County, Northeast China - Chao Zhao; Xiaoqiang Li; Xinying Zhou; Keliang Zhao; Qing Yang (Advances in Meteorology)
Pollen samples from peat sediments on the south bank of the Heilongjiang River in northern Northeast China (NE China) were analyzed to reconstruct the historical response of vegetation to climate change since 7800 cal yr BP. Vegetation was found to have experienced five successions from cold-temperate mixed coniferous and broadleaved forest to forest-steppe, steppe-woodland, steppe, and finally meadow-woodland. From 7800 to 7300 cal yr BP, the study area was warmer than present, and Betula, Larix, and Picea-dominated mixed coniferous and broadleaved forests thrived. Two cooling events at 7300 cal yr BP and 4500 cal yr BP led to a decrease in Betula and other broadleaved forests, whereas herbs of Poaceae expanded, leading to forest-steppe and then steppe-woodland environments. After 2500 cal yr BP, reduced temperatures and a decrease in evaporation rates are likely to have resulted in permafrost expansion and surface ponding, with meadow and isolated coniferous forests developing a resistance to the cold-wet environment. The Holocene warm period in NE China (7800–7300 cal yr BP) could have resulted in a strengthening of precipitation in northernmost NE China and encouraged the development of broadleaved forests.